Dinamika Kesulitan Siswa Kelas III dalam Menyelesaikan Operasi Hitung perkalian Matematika Di MI Al-Ma’arif - Fadila, Fauziah Nur (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2019)
Mathematics is one of the core subjects that plays an essential role in developing logical and systematic thinking skills among elementary school students. Multiplication, as one of the fundamental arithmetic operations, serves as the basis for understanding more complex mathematical concepts such as division, fractions, and algebra. However, many third-grade students still face difficulties in mastering multiplication, both conceptually and procedurally. This study aims to describe the dynamics of studynts’ difficulties in solving multiplication operations, the contributing factors, and the strategies used to overcome them. This research employed a descriptive qualitative approach with a case study design. The research was conducted at MI Al-Ma’arif Kota Sorong during the 2024/2025 academic year, involving 20 students selected through purposive sampling. Data were collected through observation, interviews, and diagnostic tests, then analyzed using Miles and Huberman’s interactive model consisting of data reduction, data display, and conclusion drawing. The results revealed that most students experienced conceptual, procedural, and application-related difficulties. Conceptual difficulties occurred because students tended to memorize multiplication facts without understanding multiplication as repeated addition. Procedural difficulties appeared in multi-digit multiplication, where students often made place-value errors. Application difficulties were found in solving word problems, where students struggled to identify the appropriate mathematical operations. In addition, affective factors such as low motivation and math anxiety also contributed to students’ poor performance. These findings indicate that multiplication learning difficulties are multidimensional, influenced by cognitive, affective, and pedagogical aspects. Therefore, teachers are encouraged to apply concrete and contextual learning approaches using visual aids and real-life examples to strengthen students’ conceptual understanding and make multiplication learning more meaningful and enjoyable.